2009
DOI: 10.1111/j.1749-6632.2009.04628.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐Lymphocyte Stimulator and a Proliferation‐Inducing Ligand Serum Levels in IgA‐Deficient Patients With and Without Celiac Disease

Abstract: IgA deficiency (IgAD) is the most common form of immunodeficiency and frequently associates with autoimmunity, especially with celiac disease (CD). The mechanisms underlying IgAD and the development of autoimmunity are still relatively unknown. Elevated B-lymphocyte stimulator (BLyS) and APRIL (a proliferation-inducing ligand) serum levels characterize several autoimmune diseases. We herein investigated BLyS and APRIL serum levels in IgAD patients with and without CD and compared these patients to CD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…BAFF represents a fundamental cytokine of the Tindependent IgA class-switching recombination system through the interaction with the common receptor TACI shared also by other proteins, such as APRIL [21]. In this study, we report elevated BAFF levels among CentralEuropean Caucasian patients with obesity, and we also demonstrate substantial dependence of differences in BAFF plasma levels on gender.…”
Section: Discussionsupporting
confidence: 57%
“…BAFF represents a fundamental cytokine of the Tindependent IgA class-switching recombination system through the interaction with the common receptor TACI shared also by other proteins, such as APRIL [21]. In this study, we report elevated BAFF levels among CentralEuropean Caucasian patients with obesity, and we also demonstrate substantial dependence of differences in BAFF plasma levels on gender.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we observed that TGF‐β mRNA expression was significantly decreased in the duodenal mucosa of dogs with IBD, whereas BAFF and APRIL mRNA were increased. Interestingly, serum BAFF and APRIL concentrations are significantly higher in humans with IgA deficiency than in healthy donors . Because BAFF and APRIL promote IgA production, their overexpression may represent a physiologic compensatory mechanism in an attempt to overcome the decrease in IgA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis of association of celiac disease and IgAD proposes an increase of B lymphocyte stimulating factors (B-lymphocyte stimulator (BLyS) and a proliferation inducing ligand -APRIL) noted in IgAD patients as an important factor. A new, large, indepth study did not reveal differences between the level of these factors in IgAD with or without concomitant celiac disease [7]. It seemed, that the possibility of destruction of the mucous membrane and occurrence of clinical symptoms due to disturbed metabolism of gliadin in the case of a lack of secretory IgA is more probable [2].…”
Section: The Most Common Humoral Immunodeficiencies In Children Selecmentioning
confidence: 85%